- Parenting self-efficacy sebagai moderator dalam hubungan mindful parenting dan stres pengasuhan pada ibu yang memiliki anak usia dini: - - Nazlah Hasni; Iswinarti; Muhamad Salis Yuniardi (Psychological Journal: Science and Practice, 2024)
Mothers of young children often experience parenting stress due to physical and emotional demands, lack of experience, and limited personal time. This condition can affect parenting processes and child development during the golden age. To understand how parenting self-efficacy (PSE) can reduce parenting stress through mindful parenting, an analysis was conducted involving 200 mothers with young children. Mindful parenting was measured using the Mindfulness in Parenting Questionnaire (MIPQ), parenting stress with the Parental Stress Scale (PSS), and PSE with the Self-Efficacy for Parenting Tasks Index (SEPTI). The results showed that PSE moderates the relationship between mindful parenting and parenting stress. The interaction coefficient of 0.0084 with a p-value of 0.024 indicates that higher PSE can strengthen the positive effects of mindful parenting in reducing parenting stress.